Effect of freezing and frozen storage on mesquite–wheat dough for panettone-like breads - Bigne, Facundo (2019)
The aim of this work was to study the viability of freezing preservation of composite wheat–mesquite dough of panettone-like bread. Three levels of replacement of wheat by mesquite flour were assayed: 15, 25 and 35% (w/w). Texture profile analysis, stress relaxation assays and dynamic oscillatory measurements were conducted to characterize the rheological behavior of thawed dough after different times of frozen storage at − 20 °C. Moisture, water activity and freezable water by DSC were measured. The damage by freezing on dough structure was analyzed by ESEM. Composite wheat–mesquite dough could undergo frozen storage without drastic rheological changes when 15–25% level of replacement was used. With the maximum level of mesquite, 35%, a less regular and crosslinked network than the control without mesquite could be observed in fresh dough. This network resulted more susceptible to damage by ice formation leading to lesser cohesiveness and elasticity of dough after thawing.